EXTRA-CURRICULAR ENGAGEMENT IN RELATION TO ENGLISH PERFORMANCE OF THE EDUCATION STUDENTS OF COLEGIO DE LA PURISIMA CONCEPCION - Villorente, Ivie L. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Extracurricular activities have long been recognized as a valuable component of a well-rounded education, offering students opportunities to explore their interests, develop essential life skills, and enhance their overall well-being. These activities extend beyond the traditional classroom setting, providing a platform for students to engage in diverse pursuits ranging from sports and arts to community service and leadership roles. While the benefits of extracurricular involvement are widely acknowledged, their impact on academic performance, particularly in English language proficiency, remains a subject of ongoing research and debate. This research delved into the intricate relationship between extracurricular engagement and English performance of education students at Colegio de la Purisima Concepcion (CPC). Specifically, this study sought to find answer to the following: level of extra-curricular engagement of education students;  level of English performance of the Education students; and to determine if there is a significant relationship between the extra-curricular engagement and the English performance of the Education students. This study adopted a quantitative-correlational research design. The participants of the study were the selected Education students from all-year levels under the College of Arts, Sciences, and Education (CASE) department of CPC.  The simple random sampling was employed in the selection of the participants of the study. The total respondents were 82 students derived from using the Slovin’s formula. This study utilized a 20-item researcher’s made questionnaire to gather the data.  The questionnaire was divided into two sections. Section A is composed of ten statements to describe the level of student’s extra – curricular engagement, and section B is composed of 10 statements to describe the level of student’s English performance. The panel of experts validated the questionnaire and it was tested for reliability before it was distributed to the respondents.  The permission to conduct the study was secured from the College of Arts, Sciences and Education of Colegio de la Purisima Concepcion School administrators. The researchers distributed the questionnaire to the identified respondents and gave them time to answer the questions by checking the box that corresponds to their answers. Upon the retrieval of the research instruments, the data was then tallied and computer-processed using Statistical Package for Social Sciences (SPSS) software, analyzed and interpreted. Frequency count and percentage were used to find out the number of respondents that belonged to a particular category.  The obtained mean scores were used to describe the extracurricular engagement and English performance of the students. Standard deviation was utilized to determine an indication of how far the individual responses to a question vary or "deviate" from the mean. To determine the relationship between the extracurricular engagement and  English performance of Education students, the Pearson product-moment correlation coefficient was used. The level of significance was set at 0.05. The results of the respondents’ responses with regards to the level of their extra-curricular engagement gained a grand mean score of 2.65, verbally interpreted as “sometimes.” Considering the statement on attending symposiums about English, results indicated that the students often attend such event; and they often participate in English enhancement programs. Sometimes they participate in cultural competition and sometimes join in English organization/club as well. However, results also revealed that the respondents never join in spoken poetry competition; and never engage themselves in a spelling bee contest or in online English competitions. The results of the respondents’ responses with regards to the level of their English performance  gained a grand mean of 3.71 described as  “above average.” The results revealed that the respondents have above average performances in  writing  essays using English language; in participating in oral recitations in their English class; and in speaking English in class. The results also revealed that the respondents have above average performance in  comprehending the English context; in speaking  English with other people; in writing the correct spelling of English word; and in  writing using the English language. Meanwhile, the results further revealed that the respondents are having trouble with their vocabularies, and are having difficulties in pronouncing English words. On the other hand, the respondents are highly inspired in learning English language. The findings revealed a complex interplay between extracurricular engagement and English performance. The students generally demonstrated above-average English performance indicating a strong foundation in the language. The result in determining the relationship between the extra-curricular engagement and the English performance of the respondents revealed a significant relationship. The result suggests that if the students are engaged in extra-curricular activities, they cannot focus in their academics especially in their English performance, but if the students do not participate in any extra-curricular activities at school, they can excel in their performance in English.